Lysophosphatidic Acid Receptor 3 Suppress Neutrophil Extracellular Traps Production and Thrombosis During Sepsis - Pei, Shengqiang; Xu, Chuansheng; Pei, Jianqiu; Bai, Ruifeng; Peng, Rui; Li, Tiewei; Zhang, Junjie; Cong, Xiangfeng; Chun, Jerold; Wang, Fang; Chen, Xi (Frontiers in Immunology, 2022)
Sepsis consists of life-threatening organ dysfunction resulting from a dysregulated response to infection. Recent studies have found that excessive neutrophil extracellular traps (NETs) contribute to the pathogenesis of sepsis, thereby increasing morbidity and mortality. Lysophosphatidic acid (LPA) is a small glycerophospholipid molecule that exerts multiple functions by binding to its receptors. Although LPA has been functionally identified to induce NETs, whether and how LPA receptors, especially lysophosphatidic acid receptor 3 (LPA3), play a role in the development of sepsis has never been explored. A comprehensive understanding of the impact of LPA3 on sepsis is essential for the development of medical therapy. After intraperitoneal injection of lipopolysaccharide (LPS), Lpar3-/-mice showed a substantially higher mortality, more severe injury, and more fibrinogen content in the lungs than wild-type (WT) mice. The values of blood coagulation markers, plasma prothrombin time (PT) and fibrinogen (FIB), indicated that the Lpar3-/- mice underwent a severe coagulation process, which resulted in increased thrombosis. The levels of NETs in Lpar3-/- mice were higher than those in WT mice after LPS injection. The mortality rate and degree of lung damage in Lpar3-/- mice with sepsis were significantly reduced after the destruction of NETs by DNaseI treatment. Furthermore, in vitro experiments with co-cultured monocytes and neutrophils demonstrated that monocytes from Lpar3-/- mice promoted the formation of NETs, suggesting that LPA3 acting on monocytes inhibits the formation of NETs and plays a protective role in sepsis. Mechanistically, we found that the amount of CD14, an LPS co-receptor, expressed by monocytes in Lpar3-/-mice was significantly elevated after LPS administration, and the MyD88-p65-NFκB signaling axis, downstream of Toll-like receptor 4 signaling, in monocytes was overactivated. Finally, after an injection of the LPA3 agonist (2S)-1-oleoyl-2-methylglycero-3-phosphothionate (OMPT), the survival rate of mice with sepsis was improved, organ damage was reduced, and the production of NETs was decreased. This suggested the possible translational value and application prospects of (2S)-OMPT in the treatment of sepsis. Our study confirms an important protective role of LPA3 in curbing the development of sepsis by suppressing NETs production and thrombosis and provides new ideas for sepsis treatment strategies.